Implementasi dan Analisis Akuntansi Persediaan Berdasarkan PSAK No. 14 pada PT. Trimitra Alkabes Mandiri - Ari Saputra, I Gusti Agung; Mandira, I Made Chandra (Universitas Teuku Umar, 2024)
PT. Trimitra Alkabes Mandiri is a trading company that functions as a distributor for aluminum sales. PT. Trimitra Alkabes Mandiri is experiencing problems due to inaccurate inventory data, which raises doubts about the company's compliance with PSAK No. 14. This service aims to socialize and evaluate whether PT's inventory accounting aligns with the supply-related statement in PSAK No. 14. The service method employs outreach and evaluation techniques to identify trends in inventory accounting analysis, drawing from PSAK No. 14. The company has conducted outreach, implemented a periodic recording system to record its inventory, and assessed its inventory using the FIFO (First In First Out) method. Based on the findings obtained, it can be concluded that PT. Trimitra Alkabes Mandiri has implemented inventory accounting properly in accordance with PSAK No. 14 concerning inventory. The suggestions and future evaluation that can be given include conducting regular employee training related to PSAK No. 14 and conducting regular internal audits to reduce the occurrence of inaccurate inventory data.